A dynamic corrective control method for congestion mitigation of hybrid AC/DC power systems. (January 2022) - Zhou, Yang; Rehtanz, Christian; Sebaa, Karim; Luo, Pei; Li, Yong; Winifred Asmah, Marilyn; Häger, Ulf
Highlights: An overall framework of dynamic corrective control method via the HVDC system for congestion alleviation is proposed. An activation mechanism is developed and direction of corrective control action is taken into account. A closed-loop control structure is designed to take the better advantages of the controllability and flexibility of HVDC to enhance the security. It can expand the application scenarios of HVDC systems to alleviate the post-contingency congestion, allow for better utilization of system assets within the transmission system. Abstract: Transmission congestion is a relatively common phenomenon that occurs in the operation of the power system. When the congestion could not be handled efficiently, it will lead to substantial economic costs for system operators. Many of the existing solutions are based on open-loop corrective methods, which do not completely guarantee good and reliable control results. However, in recent years, the voltage source converter (VSC)-based high voltage direct current (HVDC) system has been widely utilized in power systems to improve the flexibility of hybrid AC/DC systems significantly. Thus, this paper proposes a dynamic corrective control (DCC) method, which takes advantage of the VSC-HVDC system to regulate power flow distribution, thereby alleviating transmission congestions. In the proposed method, the sensitivity of VSC-HVDC power adjustment to AC line power changes is first analyzed to explain the power relationship between the AC system and the HVDC system. Based on this, an activation mechanism for the control actions is developed to avoid introducing invalid corrective control loops. The action rules of the corrective control process are further analyzed in detail, while the method for determining the action direction of the VSC-HVDC power adjustment in the control process is formulated. In order to acquire more reliable control results, a closed-loop control structure is established to provide more controllability. Validation of the effectiveness of the proposed method with time-domain simulation shows that the method can effectively alleviate the AC line congestion within the control range of the VSC-HVDC system and hence, significantly improving the dynamic security of the hybrid AC/DC power system.